Identification of Plasmodium falciparum specific translation inhibitors from the MMV Malaria Box using a high throughput in vitro translation screen. (December 2016) - Ahyong, Vida; Sheridan, Christine; Leon, Kristoffer; Witchley, Jessica; Diep, Jonathan; DeRisi, Joseph
Abstract Background A major goal in the search for new anti-malarial compounds is to identify new mechanisms of action or new molecular targets. While cell-based, growth inhibition-based screening have enjoyed tremendous success, an alternative approach is to specifically assay a given pathway or essential cellular process. Methods Here, this work describes the development of a plate-based, in vitro luciferase assay to probe for inhibitors specific to protein synthesis inPlasmodium falciparum through the use of an in vitro translation system derived from the parasite. Results Using the Medicines for Malaria Venture's Malaria Box as a pilot, 400 bioactive compounds with minimal human cytotoxicity profiles were screened, identifying eight compounds that displayed greater potency against theP. falciparum translation machinery relative to a mammalian translation system. Dose–response curves were determined in both translation systems to further characterize the top hit compound (MMV008270). Conclusions This assay will be useful not only in future anti-malarial screening efforts but also in the investigation ofP. falciparum protein synthesis and essential processes inP. falciparum biology.